Direct healthcare professional communications: A quantitative assessment study - Hajar Alsaleh; Thamir M. Alshammari (Wiley, 2021)
Abstract A retrospective observational study evaluated the direct healthcare professional communication (DHPC) letters disseminated by the Saudi Food and Drug Authority (SFDA) and their compliance with the pharmacovigilance guidelines. The study was utilized all DHPC letters available on the SFDA website, which is intended to communicate drug safety information to healthcare professionals (HCPs). Then, the letters were evaluated based on DHPC letter requirements approved in the European Medicines Agency (EMA) pharmacovigilance guidelines. Statistical analyses were conducted utilizing statistical analysis software (SAS® version 9.4). In June 2020, 169 letters were retrieved from the SFDA website. Most of the letters had the marketing authorization holder's logo (97%) and mentioned the date of letter issuance (98.8%). The most frequently discussed safety issues were hyperkalemia risk associated with combining renin-angiotensin-aldosterone system (RAAS) medications (10.6%) and cardiac risks (9%). Antineoplastic and immunosuppressant classes were associated with a majority of DHPC letters (15% for each category). A significant percentage of DHPC letters (10%) did not mention an agreement statement with SFDA, and 42 letters did not include marketing authorization holders (MAHs) contact information. The qualified persons responsible for pharmacovigilance and medical directors had signed most of the DHPC letters (51% and 46%, respectively). Many letters mentioned the details of reporting information to both SFDA and an MAH (82%). Moreover, 66% of the DHPC letters presented safety information within the 2‐page limit. In conclusion, the DHPC letters disseminated by MAHs in Saudi Arabia have an acceptable level of compliance with the guidelines.